Let
and g be the inverse of
.
Then the value of
is
Clarification :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If g is the inverse of f, then, ⇒ g o f ( x ) = x ⇒ g ( f ( x ) ) = x Differentiating both sides with respect to x.
g ′ ( f ( x ) ⋅ f ′ ( x ) = 1 On observing, f ( 2 ) = 0 .
g ′ ( f ( 2 ) ) ⋅ f ′ ( 2 ) = 0 ⇒ g ′ ( 0 ) ⋅ f ′ ( 2 ) = 1
Now finding f ′ ( x ) from given integral using second fundamental theorem of calculus,
f ′ ( x ) = 1 + x 4 x f ′ ( 2 ) = 1 7 2
g ′ ( 0 ) = 2 1 7